COVID-19 and Abdominal Transplant: A Stepwise Approach to Practice During Pandemic Conditions. Issue 11 (November 2020) - Syed, Shareef M.; Gardner, James; Roll, Garrett; Webber, Allison; Mehta, Neil; Shoji, Jun; Adelmann, Dieter; Niemann, Claus; Braun, Hillary J.; Mello, Anna; Yao, Francis; Posselt, Andrew; et al.
Abstract : Background: The novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) disease has transformed innumerable aspects of medical practice, particularly in the field of transplantation. Main Body: Here we describe a single-center approach to creating a generalizable, comprehensive, and graduated set of recommendations to respond in stepwise fashion to the challenges posed by these conditions, and the underlying principles guiding such decisions. Conclusions: Creation of a stepwise plan will allow transplant centers to respond in a dynamic fashion to the ongoing challenges posed by the COVID-19 pandemic.